Mitigation of soil nitrous oxide emissions during maize production with basalt amendments - Chiaravalloti, Isabella; Theunissen, Nicolas; Zhang, Shuang; Wang, Jiuyuan; Sun, Fengchao; Ahmed, Ayesha A.; Pihlap, Evelin; Reinhard, Christopher T.; Planavsky, Noah J. (Frontiers in Climate, 2023)
Nitrous oxide (N2O) is a potent and long-lived greenhouse gas that accounts for roughly 6% of global anthropogenic greenhouse gas emissions, and it has risen from its preindustrial concentration of 270 ppb N2O to 332 ppb N2O as a result of human activities. The majority of anthropogenic N2O emissions (52-80%) come from agricultural settings due to high rates of reactive nitrogen fertilizer application. Amending soils with fine-grained basalt is gaining traction as a carbon dioxide removal (CDR) pathway, and model simulations suggest that this process may also significantly decrease soil N2O emissions. Here, we provide empirical constraints on the impact of enhanced basalt weathering on soil N2O fluxes by continuously measuring N2O fluxes from large-scale maize mesocosms in a greenhouse setting. We observe significant decreases in cumulative N2O emissions (between 29-32%) from mesocosm systems with basalt addition. Using a machine learning framework, we find that basalt application rate, soil pH, and surface soil moisture are the strongest levers on N2O emissions depending on the system settings. These results provide empirical support for a potentially significant co-benefit of deploying enhanced rock weathering of silicates (ERW) on managed lands, particularly those subject to elevated rates of reactive nitrogen input.